2017
DOI: 10.2991/jsta.2017.16.3.6
|View full text |Cite
|
Sign up to set email alerts
|

Improved Confidence Intervals for the Ratio of Coefficients of Variation of Two Lognormal Distributions

Abstract: The problem of estimating the ratio of coefficients of variation of two independent lognormal populations is considered. We propose two closed-form approximate confidence intervals (CIs), one is based on the method of variance estimate recovery (MOVER), and another is based on the fiducial approach. The proposed CIs are compared with another CI available in the literature. Our new confidence intervals are very satisfactory in terms of coverage properties even for small samples, and better than other CIs for sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 17 publications
0
27
0
1
Order By: Relevance
“…Table 1 records the 95% confidence interval for the ratio of the two coefficients of variation assuming that the data are obtained from independent lognormal distributions obtained by the methods discussed in this paper. Note that the MOVER method is identical to the Log method and Hasan and Krishnamoorthy [5] showed that results from the improved version of the MOVER method are still similar to those obtained by the Log method. Hence, both the MOVER method and its improved version are not included in the calculations.…”
Section: Real Data Examplementioning
confidence: 82%
See 2 more Smart Citations
“…Table 1 records the 95% confidence interval for the ratio of the two coefficients of variation assuming that the data are obtained from independent lognormal distributions obtained by the methods discussed in this paper. Note that the MOVER method is identical to the Log method and Hasan and Krishnamoorthy [5] showed that results from the improved version of the MOVER method are still similar to those obtained by the Log method. Hence, both the MOVER method and its improved version are not included in the calculations.…”
Section: Real Data Examplementioning
confidence: 82%
“…Likelihood ratio Bartlett correction (5,5,5) 0.0658 0.0512 (5,10,15) 0.0646 0.0524 (10,10,10) 0.0565 0.0495 (10,15,20) 0.0529 0.0487 (50, 50, 50) 0.0544 0.0523…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Simultaneous confidence intervals for the differences in the coefficients of variation of log-normal distributions were proposed by Thangjai, Niwitpong & Niwitpong (2016) and Thangjai, Niwitpong & Niwitpong (2020a). Moreover, Nam & Kwon (2017) and Hasan & Krishnamoorthy (2017) studied the confidence intervals for the ratio of coefficients of variation of two log-normal distributions.…”
Section: Introductionmentioning
confidence: 99%
“…Jafari and Kazemi [14] developed a parametric bootstrap (PB) approach. Some statisticians improved these tests for symmetric distributions [15][16][17][18][19][20][21][22][23]. The problem of comparing two or more CVs arises in many practical situations [24][25][26].…”
Section: Introductionmentioning
confidence: 99%